2013
DOI: 10.5513/jcea01/14.2.1232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compost on antioxidant components and fruit quality of sweet pepper (capsicum annuum L.)

Abstract: In order to determine the effect of compost (CO) on antioxidant compounds and fruit quality of sweet pepper (Capsicum annum L.), an experiment was conducted in open field. Treatments consisted of four levels of compost (0, 5, 10 and 15 ton ha -1 ).The experiment was designed in randomized block design with three replications. Compost treatments positively affected fruit antioxidant compounds of pepper (antioxidant activity, total phenolic and carbohydrate content).But, no significant difference was found in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
6
12
0
Order By: Relevance
“…Oregon, in assessing the effects of municipal solid waste compost (MSWC) mixed with soil, in different ratios, without fertigation. Aditionally, this average was similar to the mean value of 4.26 ˚Brix, determined by Aminifard et al [36] in fruits of sweet pepper cv. California Wonder, developed under in field, whose fertilization consisted of four levels of compost (0, 5, 10 and 15 t•ha −1 ) and their conclusion was that fruits harvested from plants that received compost had significantly greater TSS than those harvested from the mineral fertilizer plots.…”
Section: Total Soluble Solidssupporting
confidence: 90%
“…Oregon, in assessing the effects of municipal solid waste compost (MSWC) mixed with soil, in different ratios, without fertigation. Aditionally, this average was similar to the mean value of 4.26 ˚Brix, determined by Aminifard et al [36] in fruits of sweet pepper cv. California Wonder, developed under in field, whose fertilization consisted of four levels of compost (0, 5, 10 and 15 t•ha −1 ) and their conclusion was that fruits harvested from plants that received compost had significantly greater TSS than those harvested from the mineral fertilizer plots.…”
Section: Total Soluble Solidssupporting
confidence: 90%
“…The highest antioxidant activity was obtained in plants with a dose of 10 tons ha -1 compost. The results obtained by Aminifard et al (2013) prove that compost has a strong impact on fruit quality and on the antioxidant compounds of pepper plants under field conditions. For these reasons, the compost may be regarded as a preliminary bioprocessing stage to improve the antioxidant effect of the fruit and the quality of the pepper.…”
Section: The Effect Of the Antioxidant Content In Soil On The Quantitmentioning
confidence: 67%
“…These include polyphenols (phenolic acids and a large group of flavonoids and anthocyanins), vitamins A and C, tocopherols, carotenoids, organic acids, calcium, selenium, chlorophyllins, glutathione, indoles, phytates, thiocyanates, and linoleic acid isomers (Szajdek and Borowska 2004). Research shows that substrates rich in humic compounds increase the quantity of antioxidants in plants (Aminifard et. al 2013, Jarosz 2006, Rimmer 2006a, Shiow and Hsin Shan 2003.…”
Section: The Effect Of the Antioxidant Content In Soil On The Quantitmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of increases in chemical characters quality of pepper fruits with NPK mineral application are in agreement with those reported by El-Bassiony et al (2010). Also, many investigators found increases in chemical characters quality of pepper fruits by application with chicken manure such as those reported by Aminifard et al (2013); Khandaker et al (2017). This result may be attributed to the synchronization of availability of the proper forms of nutritive elements via organic or inorganic fertilization.…”
Section: Recorded Datamentioning
confidence: 85%